Effects of Supplementation with Natural Antioxidants on Oocytes and Preimplantation Embryos - Maria Cristina Budani; Gian Mario Tiboni (MDPI AG, 2020)
For most infertile couples, in vitro fertilization (IVF) represents the only chance to conceive. Given the limited success of IVF procedures, novel approaches are continuously tested with the aim of improving IVF outcomes. Growing attention is devoted today to the potential benefit of natural antioxidants in the optimization of infertility treatments. This review summarizes current data in this context, focusing on both experimental studies on oocytes/embryos and clinical trials on antioxidants supplementation. Based on information gained from experimental studies, antioxidant supplementation may have beneficial effects on IVF outcomes in terms of quality and cryotolerance of in vitro produced embryos, together with positive effects on in vitro maturation oocytes and on early embryonic development. Unfortunately, from the clinical side, there is a paucity of evidence favoring the protective qualities of antioxidants. Among the antioxidants considered, coenzyme Q10 may be regarded as one of the most promising for its positive role in rescuing the oxidative stress-induced damages, but further data are needed. It is concluded that further trials are necessary to characterize the potential clinical value of antioxidants in IVF treatments.